1993
DOI: 10.1139/l93-033
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic response of bridges under travelling loads

Abstract: In spite of a number of analytical and experimental investigations on the dynamic response of bridges to moving vehicle loads, the controlling parameters that govern the response have not been clearly identified. This has, in turn, inhibited the development of rational design procedures. Based on an analytical investigation of the response of a simplified beam model traversed by a moving mass, the present study identifies the governing parameters. The results clearly show why attempts to correlate the response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 5 publications
0
28
0
Order By: Relevance
“…All but one value of the calculated dynamic load allowance were less than unity, suggesting that the peak responses due to dynamic loading events were generally less than those for corresponding static load events. However, the dynamic load allowance is known to be dependent on a wide variety of factors, including the vehicle weight, speed, suspension characteristics and axle configuration, as well as the road surface roughness and irregularities along the bridge and approach spans, and bridge stiffness and mass considerations (Paultre et al 1992;Humar and Kashif 1993). The results reported herein relate to a single truck configuration and road condition existing at the time of the measured events.…”
Section: Dynamic Load Allowancementioning
confidence: 96%
“…All but one value of the calculated dynamic load allowance were less than unity, suggesting that the peak responses due to dynamic loading events were generally less than those for corresponding static load events. However, the dynamic load allowance is known to be dependent on a wide variety of factors, including the vehicle weight, speed, suspension characteristics and axle configuration, as well as the road surface roughness and irregularities along the bridge and approach spans, and bridge stiffness and mass considerations (Paultre et al 1992;Humar and Kashif 1993). The results reported herein relate to a single truck configuration and road condition existing at the time of the measured events.…”
Section: Dynamic Load Allowancementioning
confidence: 96%
“…There are various representations of moving rail vehicles used in dynamic analyses, differing in terms of mathematical and physical accuracy [2,6,7,8,9,12,16]. The most popular models are ( The first two models can be used for determining the dynamic response of bridge yet without analysing the behaviour of vehicle and vehicle-structure interaction.…”
Section: Mechanical Models Of Rail Vehicles In Relation To the En-199mentioning
confidence: 99%
“…The first analytical studies evaluated the maximum dynamic amplification factors relative to the deflection of simple beams and different boundary conditions at the supports [4,5]. In 1993, Humar and Kashif published a study -3-in which they showed that dynamic amplification factors depend on the velocity and weight of the vehicle [6]; it criticised the continued evaluation of DAFs on the basis of a single parameter [6,7]. In 1997, Henchi et al extended analytical studies to the subject of continuous bridges [8].…”
Section: Research Into Dynamic Amplification Factorsmentioning
confidence: 99%